Intention to Use E-wallet Dilihat dari Perceived Usefulness, Perceived Ease of Use, Perceived Security, dan Trust - Endah Pri Ariningsih; Wijayanti Wijayanti; Mahendra Galih Prasaja (Universitas Proklamasi 45, 2022)
Currently, the lifestyle of modern society is changing, due to the support of increasingly sophisticated technology. Technology makes it easy for users to carry out various activities very easily. One form of this technology is the smartphone, it’s a multifunctional tool that can replace various products and functions in one hand. In addition to entertainment, smartphones are also used for work, and even make financial transactions very easily. However, risks can occur with the existence of these advanced technologies. Perceptions of the ease of use of technology and consumer confidence can reduce the risks faced. This study uses an e-wallet object for further analysis. The purpose of this study was to determine the factors that influence the intention to use the e-wallet. The sample of this study was young people, from 300 students who were determined by quota sampling technique, while the research instrument used a questionnaire that was tested for validity and reliability before data analysis. A multiple linear regression analysis methods was used to test the hypothesis proposed in this study. The results of this study indicate that perceived usefulness, perceived ease of use, and trust have a significant and positive effect on the intention to use the e-wallet, while perceived security has no significant effect.